2018
DOI: 10.1002/cc.20299
|View full text |Cite
|
Sign up to set email alerts
|

Student Success in Developmental Math Education: Connecting the Content at Ivy Tech Community College

Abstract: 3 This chapter considers difficulties with traditionally organized developmental math course sequences from the literature and practice. We then report initial student success findings following the system-wide implementation of a corequisite model in developmental math.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…What appears to have mattered most for students in these data were forms of academic capital that serve students in a variety of university contexts, not just in mathematics courses. If one assumes that corequisite remediation should have a significant influence in facilitating student achievement, as has been reported in various other studies (e.g., Denley 2016; Kashyap and Matthew 2017; Barbitta and Munn 2018;Royer and Baker 2018), then these negative results highlight the importance of attending to how a course's corequisite model is designed and implemented. In addition to factors like student and teacher buy-in noted by Campbell and Cintron (2018), the Dana Center Mathematics Pathways (2018) project discuss that factors such as:…”
Section: Discussionmentioning
confidence: 83%
“…What appears to have mattered most for students in these data were forms of academic capital that serve students in a variety of university contexts, not just in mathematics courses. If one assumes that corequisite remediation should have a significant influence in facilitating student achievement, as has been reported in various other studies (e.g., Denley 2016; Kashyap and Matthew 2017; Barbitta and Munn 2018;Royer and Baker 2018), then these negative results highlight the importance of attending to how a course's corequisite model is designed and implemented. In addition to factors like student and teacher buy-in noted by Campbell and Cintron (2018), the Dana Center Mathematics Pathways (2018) project discuss that factors such as:…”
Section: Discussionmentioning
confidence: 83%
“…Prior studies have shown that a substantial number of students tend to be underplaced, which means that they are required to take a developmental course even though they likely could have passed a for-credit course (e.g., Leeds & Mokher, 2020;Scott-Clayton et al, 2014). Under the corequisite model, students are less likely to be harmed by underplacement because they can enroll directly in college-level courses (Jaggars et al, 2015;Logue et al, 2019;Ran & Lin, 2019;Royer & Baker, 2018). Corequisite courses may also improve student motivation and reduce stigma because students are placed in a college-level course and provided opportunities to earn college credit (Edgecombe, 2011;Ran & Lin, 2019;Royer & Baker, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Under the corequisite model, students are less likely to be harmed by underplacement because they can enroll directly in college-level courses (Jaggars et al, 2015;Logue et al, 2019;Ran & Lin, 2019;Royer & Baker, 2018). Corequisite courses may also improve student motivation and reduce stigma because students are placed in a college-level course and provided opportunities to earn college credit (Edgecombe, 2011;Ran & Lin, 2019;Royer & Baker, 2018). In addition, corequisite courses often result in curricular changes that improve alignment and relevance through the pairing of developmental skills with college-level assignments (Miller et al, 2020;Ran & Lin, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Corequisite learning, widely discussed in CCA and CCG literature, has been found to facilitate success in gateway courses, including College Algebra (Berryman & Short, 2010;Brower et al, 2017;Denley, 2016;Logue & Watanabe-Rose, 2014;Mireles, Acee, and Gerber, 2014;Royer & Baker, 2018). This instructional model is proposed as a way to increase gateway success through participation in the college-level course alongside a concurrent course using the concept of "just-in-time academic support" (Complete College America, 2019), with remediation and support occurring in real time with gateway course learning.…”
mentioning
confidence: 99%